Genomic comparative analysis of Ophiocordyceps unilateralis sensu lato - Lu, Yingling; Tang, Dexiang; Liu, Zuoheng; Zhao, Jing; Chen, Yue; Ma, Jinmei; Luo, Lijun; Yu, Hong (Frontiers in Microbiology, 2024)
Ophiocordyceps unilateralis sensu lato is a common pathogenic fungus of ants. A new species, O. fusiformispora, was described based on morphology and phylogenetic evidence from five genes (SSU, LSU, TEF1α, RPB1, and RPB2). The whole genomes of O. fusiformispora, O. contiispora, O. subtiliphialida, O. satoi, O. flabellata, O. acroasca, and O. camponoti-leonardi were sequenced and annotated and compared with whole genome sequences of other species in O. unilateralis sensu lato. The basic genome-wide characteristics of the 12 species showed that the related species had similar GC content and genome size. AntiSMASH and local BLAST analyses revealed that the number and types of putative SM BGCs, NPPS, PKS, and hybrid PKS-NRPS domains for the 12 species differed significantly among different species in the same genus. The putative BGC of five compounds, namely, NG-391, lucilactaene, higginsianin B, pyripyropene A, and pyranonigrin E were excavated. NG-391 and lucilactaene were 7-desmethyl analogs of fusarin C. Furthermore, the 12 genomes had common domains, such as KS-AT-DH-MT-ER-KR-ACP and SAT-KS-AT-PT-ACP-ACP-Te. The ML and BI trees of SAT-KS-AT-PT-ACP-ACP-Te were highly consistent with the multigene phylogenetic tree in the 12 species. This study provided a method to obtain the living culture of O. unilateralis sensu lato species and its asexual formed on the basis of living culture, which was of great value for further study of O. unilateralis sensu lato species in the future, and also laid a foundation for further analysis of secondary metabolites of O. unilateralis sensu lato.